2017
DOI: 10.5455/jice.20161204021549
|View full text |Cite
|
Sign up to set email alerts
|

The adjuvant use of calcium fructoborate and borax with etanercept in patients with rheumatoid arthritis: Pilot study

Abstract: Objective:This study was designed to evaluate the effects calcium fructoborate (CFB) and sodium tetraborate (NTB) as supplements in Iraqi patients with active rheumatoid arthritis (RA) maintained on etanercept.Materials and Methods:A double-blind randomized placebo-controlled clinical trial with 60 days treatment period was carried out at Baghdad Teaching Hospital, Medical city, Baghdad, Iraq. Eighty RA patients were randomized into three groups to receive either 220 mg/day CFB, 55 mg/day NTB in capsule dosage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 44 publications
(51 reference statements)
0
3
1
1
Order By: Relevance
“…Ahmed et al observed a higher frequency of 88% among Iraqi females with RA, with a mean age of 49.5±13.9 years [21]. It also contrasts from the findings of Hussain and colleagues [22]. Smoking was found to be present in 21.7% of RA patients in the current study, which is higher than the 17.4% reported by Mathkhor et al [23].…”
Section: Discussioncontrasting
confidence: 93%
“…Ahmed et al observed a higher frequency of 88% among Iraqi females with RA, with a mean age of 49.5±13.9 years [21]. It also contrasts from the findings of Hussain and colleagues [22]. Smoking was found to be present in 21.7% of RA patients in the current study, which is higher than the 17.4% reported by Mathkhor et al [23].…”
Section: Discussioncontrasting
confidence: 93%
“…Boron supports bone health in postmenopausal women, reducing the urinary loss of the minerals calcium, magnesium, and phosphorus, which are essential for bone-building (15). Lower serum levels of boron have been shown in individuals with both rheumatoid arthritis (RA) and osteoarthritis (OA) (16,17). In patients with RA is recorded a significant lower serum boron level when comparing to patients without RA.…”
Section: Discussionmentioning
confidence: 99%
“…The microbiota influences the health of the body through the “axes” already formulated and studied in the literature: the “gut-brain” axis, “gut-immunity” axis, “gut-bone” axis, “gut-cartilage” axis, “gut-heart” axis, “gut-lung” axis, and “gut-thyroid” axis [ 111 ]. This may explain the beneficial role of B in preventing certain diseases, such as OA [ 115 ], osteoporosis [ 154 ], rheumatoid arthritis [ 155 ], cardiovascular inflammation [ 18 , 131 , 156 ], depression [ 157 ], obesity [ 158 ], diabetes [ 159 ], viral and bacterial infections [ 133 , 160 ], and thyroid diseases [ 161 ].…”
Section: Perspectivesmentioning
confidence: 99%